Содержание ω-6 и ω-3 пнжк в липидах сыворотки крови крыс, получавших высокоолеиновое подсолнечное масло. = ω-6 and ω-3-pufa contents in serum lipids of rats, fed high-oleic acid sunflower oil - Khodakov, I. V.; Levitsky, A. P.; Topov, I. P. (Journal of Education, Health and Sport, 2016)
Khodakov I. V., Levitsky A. P., Topov I. G. Содержание ω-6 и ω-3 пнжк в липидах сыворотки крови крыс, получавших высокоолеиновое подсолнечное масло. = ω-6 and ω-3-pufa contents in serum lipids of rats, fed high-oleic acid sunflower oil. Journal of Education, Health and Sport. 2016;6(9):513-523. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154699 http://ojs.ukw.edu.pl/index.php/johs/article/view/3873 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 21.09.2016. УДК 616.33:342.092 СОДЕРЖАНИЕ ω-6 И ω-3 ПНЖК В ЛИПИДАХ СЫВОРОТКИ КРОВИ КРЫС, ПОЛУЧАВШИХ ВЫСОКООЛЕИНОВОЕ ПОДСОЛНЕЧНОЕ МАСЛО И. В. Ходаков, А. П. Левицкий, И. Г. Топов ГУ «Институт стоматологии и челюстно-лицевой хирургии НАМН Украины» г. Одесса, Украина Резюме Высокоолеиновое подсолнечное масло, в отличие от высоколинолевого, увеличивает в печени образование и секрецию ЛПОНП, стимулирует синтез ω-3 ПНЖК и снижает образование ω-6 ПНЖК. Ключевые слова: высокоолеиновое подсолнечное масло, липиды сыворотки, ω-6 ПНЖК, ω-3 ПНЖК. ω-6 and ω-3-PUFA contents in serum lipids of rats, fed high-oleic acid sunflower oil I. V. Khodakov, A. P. Levitsky, I. G. Topov SE «The Institute of Stomatology and Maxillofacial surgery of the National acаdemie of medical science of Ukraine», Odessa, Ukraine Summary Aim: To determine of high-oleic acid sunflower oil (HOASO) actions on ω-6 and ω-3 PUFA contents in rat serum lipids. Materials and Methods: Rats received the hemi-synthetic ration with 5 % HOASO. For comparison, the other group received the such ration but with 5 % high-linoleic acid sunflower oil during 30 days. The contents of triglycerides (TG) and cholesterol (CH) in serum and liver were determined enzymatic methods. The contents of fatty acids in serum lipids were determined chromatographic methods. Results: HOASO increased in the serum contents of TG and ω-3-PUFA, decreased contents of TG and CH in liver and decreased contents of ω-6-PUFA in serum lipids. Conclusion: HOASO increase of synthesis very low density lipoproteins in liver and ameliorate of the ω-6/ω-3 PUFA ratio. Keywords: high-oleic acid sunflower oil, serum lipids, ω-6-PUFA, ω-3-PUFA.